A Comprehensive Study on Physical, Mechanical, and Thermal Properties of Poly(Ethylene Terephthalate) Filled by Micro‐ and Nanoglass Flakes. Issue 3 (16th December 2019) - Miri, Fatemeh S.; Ehsani, Morteza; Khonakdar, Hossein A.; Kavyani, Behjat
Abstract : Polyethylene terephthalate (PET) composites containing micro‐ and nanoglass flakes were prepared by melt blending. The percentage of nanoglass flakes was varied from 0.5, 1, 2, and 3 wt% and the concentration of microglass flakes was 1, 3, and 5 wt%. The effect of glass flake on morphology, physical, mechanical, and thermal properties of PET was studied using scanning electron microscopy (SEM), energy‐dispersive X‐ray analysis (EDXA), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), dynamic mechanical thermal analysis (DMTA), X‐ray diffraction (XRD), and tensile test. The observations showed that both types of particles were dispersed in PET, homogeneously, though microglass flakes had better dispersion compared with their nanosized counterparts. According to DSC thermogram, the crystallization rate and temperature of PET increased with incorporation of both types of glass flakes. The crystallization rate of PET was increased from 31.41% to 34.25% with the addition of 1 wt% of nanoglass flakes. Moreover, the onset of thermal degradation increased more than 9°C with the addition of micro‐ and nanoglass flakes. Based on the mechanical viewpoint, the Young's modulus of PET was improved by the addition of both micro‐ and nanoglass flakes. On the other hand, the tensile strength of PET was decreased from 45.4 MPa to 31.3 MPa using 1 wt% of nanoglass flakes. According to X‐ray diffractometry, using of micro‐ and nanoglass flakes resulted in the decrement of PET crystallites. Whereas, the size of crystallites was lower than microglass flakes, in the case of using nanoglass flakes. J. VINYL ADDIT. TECHNOL., 26:380–389, 2020. © 2019 Society of Plastics Engineers